Extraction, identification, characterization of biological activities of Nitraria retusa flavonoids and enzymatic synthesis of acylated derivatives of these molecules - Hadj Salem, Jamila (HAL CCSD, 2009)
The present work firstly consisted in studying the extraction and the identification of major flavonoids contained in Nitraria retusa leaves and evaluating their biological activities. Four flavonoids were identified in extracts and fractions: isorhamnetin, isorhamnetin-3-O-glucoside and the two isomers isorhamnetin-3-O-rutinoside and isorhamnetin-3-O-robinobioside. The evaluation of the biological activities of extracts and fractions of N. retusa allowed to establish a linear relationship between their antioxidant and antiproliferative activities and their total flavonoids content, the most enriched exhibiting the highest activities. The nature of the flavonoids present in the extracts and fractions was shown to be important too. Thus, the strong xanthine oxidase inhibition activity and the high DPPH radical scavenging capacity observed for the chloroform fraction can be attributed to its high content in the aglycone flavonoid isorhamnetin, a structural analogue of quercetin which is well known for its antioxidant activities. In a second part, the enzymatic acylation of isoquercitrin as a model compound and isorhamnetin-3-O-glucoside was studied in order to improve their properties. The enzymatic acylation of isoquercitrin by fatty acid ethyl esters of different chain lengths, catalyzed by the lipase B of Candida antarctica, showed that the performance of the reaction is inversely proportional to the acyl donor chain length. Similar results were obtained when acylating the isorhamnetin-3-O-glucoside. The activities of isoquercitrin and isorhamnetin-3-O-glucoside esters were determined and compared to that of initial flavonoids. Esters exhibited higher antiproliferative towards Caco2 cells and xanthine oxidase inhibition activities than original compounds. Finally, this work led to a better understanding of the structure-activity relationship of flavonoids and their acylated derivatives Ce travail a consisté, dans un premier temps, à extraire et à identifier les flavonoïdes majeurs contenus dans les feuilles ...